Risk factors associated with acute pancreatitis in diabetic ketoacidosis patients: a 11-year experience in a single tertiary medical center and comprehensive literature review - Chen, Yifei; Bo, Yan; Han, Zhuanzhuan; Chen, Mengjie (Frontiers in Medicine, 2025)
ObjectiveTo identify independent risk factors and predictive markers for acute pancreatitis (AP) in patients with diabetic ketoacidosis (DKA).MethodsHere, we reported a 11-year experience in a single tertiary medical center and conduct a systematic review of acute pancreatitis in diabetic ketoacidosis patients (DKA-AP). 1,941 cases were included. First retrospective cohort study analyzed clinical data from 45 patients with DKA-AP and 45 matched controls with DKA alone (DKA-nonAP) admitted to Yangzhou University Affiliated Hospital (2013–2024). Baseline characteristics included BMI, hyperlipidemia history, and serological profiles. Secondly we retrieved clinical studies of DKA-AP from PubMed database system and analyzed these clinical data in depth.ResultsSignificant differences were observed in BMI: median [IQR] = 26.30 [22.15–28.40] vs. 23.20 [20.70–25.35] kg/m2, p = 0.031, hyperlipidemia history (26.7% vs. 4.4%, p = 0.004), abdominal pain duration (3 vs. 0 days, p < 0.001), and lipid profiles TC: median [IQR] = 7.71 [5.60–11.66] vs. 4.86 [4.22–6.52] mmol/L, p < 0.001; TG: median [IQR] = 11.90 [4.71–15.84] vs. 1.60 [0.89–3.64] mmol/L, p < 0.001. Logistic regression identified TC (OR = 1.455, 95% CI: 1.196–1.769), TG (OR = 2.046, 95% CI: 1.202–3.484), and abdominal pain duration (OR = 3.892, 95% CI: 2.173–6.972) as independent risk factors. Receiver operating characteristic curve (ROC) analysis demonstrated strong predictive performance (combined AUC = 0.933, sensitivity = 93.3%, specificity = 73.3%). Moreover, we found 11 clinical studies investigating DKA-AP. Cumulatively, 1,851 patients were studied, including 3 interventional studies, 1 genetic observational study, and 7 cohort studies exploring risk factors.ConclusionElevated TC, TG, and prolonged abdominal pain duration are key predictors of DKA-AP. These factors enhance early diagnosis and clinical management in Yangzhou, China.